The impact of physical features on user attachment to Kuala Lumpur City Centre (KLCC) Park, Malaysia - Ayeghi, Atefeh; Ujang, Norsidah (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2014)
The relationship between individuals and places is conceived as place attachment. Due to fast urbanization in Malaysia, the sense of place and identity of places within the urban centers are weakening even while recreational areas are growing as one of the most essential areas in the city (DBKL, 2003). This paper discusses the impact of physical features of an urban park on user attachment to the park with reference to KLCC Park in Kuala Lumpur. Field observation was used to identify the physical features of KLCC Park and questionnaire survey was conducted involving 330 park users to gauge the influence of physical features on users’ attachment. The participants were selected randomly from those who used the park. The research found that physical features influenced users’ functional attachment. In addition, active features such as water features had a strong effect on user attachment compared with passive features. The results highlighted the importance of water features in fulfilling user needs, in particular, the passive engagement needs. These findings may assist urban managers and urban designers to create attractive recreational places in the city thus contributing to the forging of stronger user attachment to the park and increase frequency of its use.